2020
DOI: 10.1002/mds.28264
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Experimental Models of α‐Synucleinopathies

Abstract: Neuroinflammation has long been associated with central nervous system pathology in α‐synucleinopathy disorders including Parkinson's disease and multiple system atrophy. In the past decade, research‐focused efforts in preclinical and experimental models have rallied around this idea, and considerable effort has been made to delineate critical neuroinflammatory processes. In this article, we discuss challenges in preclinical research, notably the use of animal models to recapitulate and dissect disease phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 130 publications
(258 reference statements)
1
28
0
Order By: Relevance
“…It has been proposed that the neuron-microglia interaction may contribute to the neuroinflammation that characterizes PD, where neurons expressing aSyn activate microglia, which in turn secrete inflammatory factors surrounding the diseased neurons, thus forming a vicious cycle [ 456 ] ( Figure 3 ). Likewise, microgliosis has been also reported in MSA, where aSyn is found aggregated mainly within oligodendrocytes [ 426 , 457 , 458 , 459 ]. This hypothesis for neuron-microglia communication in synucleinopathies is further supported by findings demonstrating an altered expression profile of various cytokines in the brains of PD patients [ 460 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 87%
“…It has been proposed that the neuron-microglia interaction may contribute to the neuroinflammation that characterizes PD, where neurons expressing aSyn activate microglia, which in turn secrete inflammatory factors surrounding the diseased neurons, thus forming a vicious cycle [ 456 ] ( Figure 3 ). Likewise, microgliosis has been also reported in MSA, where aSyn is found aggregated mainly within oligodendrocytes [ 426 , 457 , 458 , 459 ]. This hypothesis for neuron-microglia communication in synucleinopathies is further supported by findings demonstrating an altered expression profile of various cytokines in the brains of PD patients [ 460 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 87%
“…[36][37][38] In a study using 11 C-DPA713, a significant increase in uptake was shown in the occipital, temporal, and parietal cortex of the brains of PD patients. 36 Significantly higher microglial activation was also shown with 18 F-DPA714 in the midbrain, frontal cortex, and putamen of PD patients relative to controls. 38 In summary, microglial activation has been evidenced in vivo by PET studies in the premotor or clinical stages of PD.…”
Section: In Vivo Evidence Of Inflammation In Pd Patientsmentioning
confidence: 94%
“…In addition to αSyn propagation, neuroin ammation has been suggested as one of the main mechanisms contributing to PD pathogenesis 4,5 . Postmortem studies using PD brain reported extensive microgliosis in the brain regions affected by synuclein pathology 4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to αSyn propagation, neuroin ammation has been suggested as one of the main mechanisms contributing to PD pathogenesis 4,5 . Postmortem studies using PD brain reported extensive microgliosis in the brain regions affected by synuclein pathology 4,6 . Besides microglia, astrocytic activation, and increased MHC-II, MHC-I expression as the adaptive immune response has also been reported to contribute to the progression of PD 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation